ABCDE Conference ECA Policy Workshop «EDUCATION AND GLOBAL DEVELOPMENT» - Voprosy Obrazovaniya Authors (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
St. Petersburg, St. Petersburg State University, Law Department January 19, 2006.World Bank organized The Annual Bank Conference on Development Economics (ABCDE) in St. Petersburg, Russia, from January 18 to January 19, 2006. A special feature of the 2006 ABCDE Conference was a half-day Policy Workshop «Education and Global Development». This workshop discussed the main education policy challenges under conditions of globalization and growing role of the knowledge economy. The Workshop agenda included issues of access and quality of primary education in development context, issues of labor market linkages, labor mobility and relevance of tertiary education. As education is a key development factor for countries and regions across the world and very important in the context of globalization, the conclusions of the Workshop could be a helpful contribution to Russia’s G8 2006 agenda.